Time operations - Silva, Cidália Ferreira (2018)
This chapter proposes four time operations—gleaning, grounding, stimulating, and transmuting—for practicing time within architecture as an expanded field. By exploring the relationships between the future-past-present through folded time as coexistence and lived time, these time operations unfold the ways to make interprojects for cultural landscape adaptability. First, the background that supports this research is presented, namely, why is it relevant and the main references with which this path was made concrete. Second, the meaning of time is defined as a way to understand what time practice is being deepened. Third, each operation is explored by describing the main features and procedures pertaining to gleaning, grounding, stimulating, and transmuting. Fourth, the chapter discussion continues by revealing the relationships between the operations, namely moving beyond the expected linear succession. The chapter concludes with a hypothesis of further future development as well as the main conclusion and key terms.